PENGARUH TERAPI CERMIN TERHADAP KEMAMPUAN GERAK PADA PASIEN STROKE DI WILAYAH KERJA PUSKESMAS KUMPULAN KABUPATEN PASAMAN - Muhammad Arif; Suci Mustika; Def Primal (JURNAL KESEHATAN PERINTIS, 2019)
Background: Stroke is a disease or functional disorder of the brain in the form of nerve paralysis due to inhibition of blood vassel flow to the brain. Based on Medikal Record data of Kumpulan Public Health Center 2016, there were 67 cases. Whereas in 2017 there were 81 cases of stroke 25 witch of them outpatients who experience weakness in the limb and have never received mirror therapy. Objective: This study was to investigate "the effect of mirror therapy on the ability of motion in stroke patients in Kumpulan Public Health Center on 2018. Method: This study used the quasi-experimental method of One Group Pretest-postest. Interventions: Mirror therapy performed 5-10 minutes, once a day, 5 times a week for 4 weeks. The sample in this study were 11 respondents. Results: This research has been conducted from February 5 to March 3, 2018. The results of statistical tests obtained p value 0,000 wich it can be concluded that there is a significant influence between the mirror therapy on the ability of motion in stroke patients in Kumpulan Public Health 2018 year. Conclusion and Suggestions: It is recommended that mirror therapy should be used as one of the nonpharmacologic therapies in patients with weak extremities either through the provision of education in educational institutions and in health services by health care provider.